Integrity Assessment of Stress Corrosion Cracking Susceptibility of Duplex UNS S32205 and Austenitic UNS S31653 Stainless Steel Reinforcements - Ulises Martin; David M. Bastidas (Metals, 2023)
Herein, the stress corrosion cracking (SCC) susceptibility of duplex (UNS S32205) and austenitic (UNS S31653) stainless steel (SS) reinforcements was evaluated using integrity assessment criteria. Mechanical properties were analyzed and compared by different SCC susceptibility factors. The integrity assessment was conducted applying Cosenza, Creazza, and Ortega ductility criteria, following three different standards (ACI 318-19, ASTM A615, and FIB). A conventional carbon steel (UNS G10080) reinforcement was also evaluated for comparative purposes, whose high residual stress value (>280 MPa) promoted a high corrosion growth rate. Duplex UNS S32205 SS grade showed a significant decrease in elongation, leading to failure after ductility assessment at high chloride concentrations. Fractographic analysis of both SS grades, duplex and austenitic, revealed less than 40% brittle areas at 8 wt.% Cl−, while UNS G10080 had over 85% at 4 wt.% Cl−.